A systematic literature review on the challenges of conducting reading comprehension assessment in senior high school - Adi Cita; Sri Hartiningsih; Estu Widodo (English Learning Innovation, 2026)
Mastering reading skills is really important to gain knowledge or to discover information from written text. In the classroom setting, the teacher needs to conduct an assessment to measure students' comprehension of reading. Assessment of reading comprehension includes methods and techniques intended to show how effectively students can read, understand, interpret, and analyze a variety of texts. The purpose of the study is to reveal the challenges faced by teachers in conducting reading comprehension assessments, both in online and face-to-face assessments. The research design of this study is a systematic literature review which applied PRISMA method. The sources of the data were taken from the articles published in journals that are indexed in SINTA. Several criteria of inclusion to the related topic of study are the relevant papers of reading assessment, papers published in 2020-2025, articles only without books or proceedings, and the content of the articles. Furthermore, the researchers analyzed the data using the cluster method, where the classification of the challenges is based on the principles in conducting assessment; validity, reliability, practicality, authenticity, and washback effect. As the result, many teachers design tests without aligning them with the course objectives. Construct validity is further undermined by unsuitable tests, which include activities that do not evaluate comprehension, unclear instructions, and an insufficient difficulty level. Reliability issues also arise due to weak item discrimination, inconsistent scoring rubrics, subjective teacher judgement, and environmental distractions that affect students’ performance. Practicality becomes another major concern as teachers face large class sizes, limited preparation time, administrative burdens, and difficulties in administering the score. Authenticity and the washback effect also contribute to assessment problems. Many reading tests failed to reflect real-world tasks or specific language used for vocational students. Teachers struggle to design authentic materials connected to students’ majors, reducing the meaningfulness of the assessment tasks. Negative washback effect occurs when outdated test formats provide little support for comprehension and skill improvement, demotivate learners, and limit opportunities for personalized feedback, especially in online classes. However, this study provided a brief view for the test makers to avoid the same challenges in developing the similar assessment.